Ethics in infectious diseases: latent challenges. Part I - Jéssica H. Guadarrama-Orozco (Permanyer, 2023)
Infectious diseases socially imply individual and community medical problems. Therefore, they require actions aimed at social processes that affect the well-being of the individuals without losing sight of social groups. Faced with this panorama, we ask ourselves: is there a direct relationship between ethics and infectious diseases? To elucidate an answer, let us remember the peak period of the COVID-19 pandemic when guidelines based on ethical principles were issued to facilitate medical decisions on allocating scarce resources in periods of maximum demand. In those moments, since there was no inclusive component of society, the decisions made produced massive criticism. The reactions demonstrated the need to analyze in detail the criteria that had been considered correct. Consequently, we affirm that bioethical principles are transcendental in medical decisions and must be examined, not only for the individual but also with a view to public health. Moreover, the acquired immunodeficiency syndrome (AIDS) epidemic has lived with us for decades, and it continues to show its tragic face in the form of new cases, chronic illnesses, and deaths. Joint United Nations Programme on HIV/AIDS brings us closer to a complex reality where the fight against disease and global health are interrelated with other problems, such as the need to reduce inequality, for which human rights, gender equality, social protection, and the development of research projects, where the ethics committees in research in community processes are constituents.